ҲАЁТ ФАОЛИЯТИ ХАВФСИЗЛИГИ СОҲАСИДА ПЕДАГОГИК ТАЪЛИМ МАЗМУНИ - Очилов, А.О.; Сададдинов, У.У. (SCIENCE and SOCIETY, 2020)
The article deals with methods of teaching life safety in vocational training. The author also investigates the stages of information presentation in teaching process.
Keywords: professional disorders; structural stages; building hypothesis; targeted education recipients; training grounds